Evaluation of students' scientific process skills through reflective worksheets in the inquiry-based learning environments. Issue 2 (3rd March 2020) - Mutlu, Ayfer
ABSTRACT: This study aimed to evaluate how 7th-grade students' scientific process skills changed in the inquiry-based learning environment through reflective worksheets. For this purpose, four inquiry-based activities related to electrical circuits were developed. Forty students enrolled in 7th grade in a public school in a mid-size city of Turkey located in the north-west region participated in the study, and they are randomly stratified into eight groups. While students carried out the activities, they used reflective worksheets, including two parts, for reflection of the development of their scientific process skills. Instructions were conducted for four weeks, and all the 32 reflective worksheets were evaluated by using the assessment rubric (for Part-I) and content analysis (for Part-II). The results obtained from both parts of the reflective worksheets showed that inquiry-based learning activities promoted students' scientific process skills such as defining the problem, formulating a hypothesis, observing and interpreting results during the inquiry-based learning process. Students also improved in terms of ability such as using scientific terms, drawing scientific and comprehensible figures, and making scientific explanations. In addition to these, it was found that students had more positive opinions about the learning process.